Compliance with the rules of military registration as the implementation of military duty by citizens of Ukraine - V. I. Strelianyi (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to a scientific study of the organisation of military registration of conscripts, persons liable for military service and reservists, which is carried out by military authorities in the context of citizens' duty to defend the Motherland. The main purpose of the article is to identify certain problems of military registration and ways of their solution through administrative and legal regulation of the activities of the bodies entrusted with the task of organising and maintaining personal and high-quality registration of conscripts, persons liable for military service and reservists.